2017
DOI: 10.12965/jer.1735134.567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 10% weight loss on simulated taekwondo match performance: a randomized trial

Abstract: The objective of the present study was to analyze the effect of 10% body mass reduction on simulated taekwondo match performance. Thirty-one male taekwondo athletes were randomly distributed in two groups: weight loss group (n= 15) – athletes in this group reduced 5% body mass per week during two successive weeks, totaling 10% body mass reduction; control group (n= 16) – athletes in this group kept their body mass constant during the 2-week period. Twenty-four hours before and after this period, athletes perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…In the study by Fortes et al, they reported that a 10% reduction in body weight of the taekwondo athletes before the competition had no effect on match performance and did not improve taekwondo skills (Fortes, Vasconcelos, Costa, Paes and Franchini, 2017). In this study, the highest average weight loss rate of taekwondo athletes before the competition during the season is 4.52±2,77 kg in males and 4.40±5.36 kg in females.…”
Section: Discussionmentioning
confidence: 41%
“…In the study by Fortes et al, they reported that a 10% reduction in body weight of the taekwondo athletes before the competition had no effect on match performance and did not improve taekwondo skills (Fortes, Vasconcelos, Costa, Paes and Franchini, 2017). In this study, the highest average weight loss rate of taekwondo athletes before the competition during the season is 4.52±2,77 kg in males and 4.40±5.36 kg in females.…”
Section: Discussionmentioning
confidence: 41%
“…There are three positions on sport performance and RWL. The first posits an improvement in sport performance (Reale et al, 2016b;Coswig et al, 2018), the second suggests no changes (Choma et al, 1995;Yang et al, 2018), while the third supports a decrease in sport performance (e.g., Camarço et al, 2016;de Fortes et al, 2017;Zubac et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a substantial but limited body of scientific research investigating the prevalence of weight-cutting in different combat sports [3,4,5,6], the different methods of weight loss [3,4,5,6,7,8], the influence on competitive performance [9,10,11,12], the physiological changes associated with weight-cutting [9,13,14,15,16,17] and methods to improve performance following weight-cutting [2,18]. Within this body of literature, there are conflicting findings on many of the topics mentioned above.…”
Section: Introductionmentioning
confidence: 99%